Matching Vector Filtering Methods For Sea Ice Motion Detection Using SAR Imagery Feature Tracking - Chaoyue Li; Gang Li; Zhuoqi Chen; Xue Wang; Xiao Cheng (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2022)
Applying feature tracking techniques to synthetic aperture radar (SAR) imagery generates high-resolution sea ice motion fields. However, the bad matching vectors still exist after the Nearest Neighbor Distance Ratio test and contaminate the derived motion fields, which need to be identified and filtered out. In this article, we propose two algorithms to eliminate such wrong matching vectors. The first employs the matching results derived by the maximum cross-correlation (MCC) method as the reference motion fields to evaluate such wrong matches. The second method employs the local spatial consistency presumption of sea ice motion fields. A Voronoi diagram is applied to slice the overlapping area of two SAR images into many fractions, and each fraction extends its size 50% outward to calculate the regional mean sea ice flow vector and standard deviation. Any vector within the fraction that exceeds 3 times the regional standard deviation will be recognized as an outlier and filtered out. Two methods are tested to two cases with strong rotation or irregular sea ice motion fields derived from Sentinel-1 imagery. The overall accuracy of our two methods is 93.9% and 98.7%, and they sacrifice 6.12% /1.22% of the correct vectors to filter out 100.0% / 94.12% of the wrong vectors for the MCC referenced filter and Voronoi fragmented filter, respectively.